1984
DOI: 10.1038/309253a0
|View full text |Cite
|
Sign up to set email alerts
|

Close genetic linkage between X-linked retinitis pigmentosa and a restriction fragment length polymorphism identified by recombinant DNA probe L1.28

Abstract: Retinitis pigmentosa (RP) is a group of retinal degeneration characterized by progressive visual field loss, night blindness and pigmentary retinopathy. Its prevalence is in the region of 1-2 in 5,000 of the general population, making it one of the commoner causes of blindness in early and middle life. Although 36-48% of RP patients are isolated cases, the remainder show autosomal dominant, autosomal recessive or X-linked modes of inheritance. The X-linked variety ( XLRP ) is found in 14-22% of RP families in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(65 citation statements)
references
References 16 publications
0
65
0
Order By: Relevance
“…Although linkage to XLRP was first established in a mixed sample of RP3 and RP2 families by Bhattacharya et al [1984], it took until recently to identify the full range of mutations in the RP3 gene, RPGR . Further mutation analysis of exon ORF15 should finally establish the importance of RPGR in other populations, and settle the question of microheterogeneity at the RP3 locus.…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although linkage to XLRP was first established in a mixed sample of RP3 and RP2 families by Bhattacharya et al [1984], it took until recently to identify the full range of mutations in the RP3 gene, RPGR . Further mutation analysis of exon ORF15 should finally establish the importance of RPGR in other populations, and settle the question of microheterogeneity at the RP3 locus.…”
Section: Future Prospectsmentioning
confidence: 99%
“…A milder phenotype is often present in female carriers, probably due to random X-inactivation. Close linkage of XLRP to markers DXS7 [Bhattacharya et al, 1984;Nussbaum et al, 1985] and OTC [Musarella et al, 1988;Chen et al, 1988;Denton et al, 1988;Wirth et al, 1988;Musarella et al, 1989] was found. Subsequent linkage analysis provided evidence for two different loci: RP2 (MIM# 312600) was positioned centromeric of DXS7, while RP3 (MIM# 312610) was telomeric of DXS7 and mapped between DXS1110 and OTC [Musarella et al, 1988;Chen et al, 1989;Musarella et al, 1990;Ott et al, 1990;Dahl et al, 1991].…”
Section: Introductionmentioning
confidence: 99%
“…The probe L.128 also shows linkage with (0-15cM) retinitis pigmentosa, another serious sexlinked disorder, further demonstrating the usefulness of these techniques (Bhattacharya et al, 1984). More X chromosome specific probes are now available and work on completing an RFLPdefined genetic map of this chromosome is well underway .…”
Section: Indirect Analysis Of Genetic Diseasementioning
confidence: 92%
“…Identification of RD genes progressed slowly from mapping the first X-linked retinitis pigmentosa (RP) gene in 1984 (Bhattacharya et al 1984) until the early 1990s, as seen in Fig. 1.…”
Section: Progress In Identifying Rd Genesmentioning
confidence: 99%